O Bike in Melbourne: A plea for more scepticism about disruption and capital, based on what we can know about one dockless bike scheme. (October 2020) - Chambers, Peter
Abstract: This paper seeks to contribute to a critical dialogue on disruption and the sharing economy by reflecting critically on O Bike's appearance and disappearance in Melbourne, Australia. Recalling the credulousness that attended the arrival of O Bike's fleet between June 2017 and 2018, this paper gives primacy to considering whether O Bike was ever about bicycles and transport, showing how the scheme aligned itself with hyped discourses of disruption and the sharing economy, whose true beneficiaries were startup entrepreneurs developing platform-based schemes seeking venture capital and unicorn status. In Melbourne, this 'success' left the city with hundreds of bicycles in its waterways, and little insight or curiosity about how this was generated by a group of individuals carrying out their professed modus operandi of 2010s tech startup culture, which has no meaningful, enduring relationship with public transport or urban cycling. This re-telling of O Bike's dispersal and fall in Melbourne seeks to focus attention within transport studies and political geography on docked and dockless public bike schemes to the occluded centrality of venture capital as a key agentic force at work in global cities in the decade just passed. The limit of this re-telling is the utopia of 2010s capitalism: unlimited profit and success without regulation or responsibility. By offering critical counterfactuals from this instantiation of dockless, it encourages policy makers to think more carefully about the value and meaning of 'sharing' platforms.